Migraine and aura triggered by normobaric hypoxia. (December 2020) - Frank, Florian; Faulhaber, Martin; Messlinger, Karl; Accinelli, Chiara; Peball, Marina; Schiefecker, Alois; Kaltseis, Katharina; Burtscher, Martin; Broessner, Gregor
Background: For future experimental studies or the development of targeted pharmaceutical agents, a deeper insight into the pathophysiology of migraine is of utmost interest. Reliable methods to trigger migraine attacks including aura are desirable to study this complex disease in vivo . Methods: To investigate hypoxia as a trigger for migraine and aura, we exposed volunteers diagnosed with migraine, with (n = 16) and without aura (n = 14), to hypoxia utilizing a hypoxic chamber adjusted to a FiO2 of 12.6%. The occurrence of headache, migraine, aura, and accompanying symptoms were registered and vital signs were collected for 6 hours under hypoxia and 2 hours of follow-up. A binary logistic regression analysis examined the probability of triggering headaches, migraines, aura, photo- and phonophobia. Findings: Of 30 participants, 24 (80.0%) developed headaches and 19 (63.3%) migraine, five (16.7%) reported aura. Two patients that developed aura never experienced aura symptoms before in their life. The increase of mean heart frequency was higher in patients developing headaches or migraine. Mean SpO2 during hypoxia was 83.39%. Conclusion: Hypoxia was able to trigger migraine attacks and aura independently of any pharmacological agent.